2023
DOI: 10.1097/meg.0000000000002592
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt insertion improves muscle mass but not muscle function or frailty measures

Abstract: Introduction Sarcopenia in cirrhosis is associated with poor outcomes. While transjugular intrahepatic portosystemic shunt (TIPS) insertion improves radiological measures of muscle mass, its impact on muscle function, performance and frailty has not been evaluated. Methods Patients with cirrhosis referred for TIPS were prospectively recruited and followed for 6 months. L3 CT scans were used to calculate skeletal muscle and adipose tissue parameters. Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Importantly, increased muscle mass post-TIPS stent has been shown to correlate with improved survival, reiterating the importance of treating sarcopenia in patients with portal hypertension [ 148 ]. In a prospective cohort study involving 12 patients, Hey et al found that muscle mass significantly improved at six months post-TIPS insertion, with the mean skeletal muscle area increasing from 139.32 ± 22.72 cm 2 to 154.64 ± 27.43 cm 2 [ 149 ].…”
Section: Treatment Of Portal Hypertensionmentioning
confidence: 99%
“…Importantly, increased muscle mass post-TIPS stent has been shown to correlate with improved survival, reiterating the importance of treating sarcopenia in patients with portal hypertension [ 148 ]. In a prospective cohort study involving 12 patients, Hey et al found that muscle mass significantly improved at six months post-TIPS insertion, with the mean skeletal muscle area increasing from 139.32 ± 22.72 cm 2 to 154.64 ± 27.43 cm 2 [ 149 ].…”
Section: Treatment Of Portal Hypertensionmentioning
confidence: 99%
“…The time course of post-TIPS HE is defined by a steep rise in HE incidence in the first month after TIPS insertion, where liver function often takes a post-procedural hit [ 29 ]. The risk of new-onset episodic or recurrent HE remains high during the first year after TIPS but with the well-known post-TIPS improvement in muscle mass and fewer stressful events, the risk seemingly stagnates or declines [ 29 , 30 , 31 , 32 , 33 , 34 ]. Most cases of post-TIPS HE respond to lactulose and rifaximin treatment, but it is noteworthy that persistent post-TIPS HE is reported in 4–10% [ 20 , 35 , 36 , 37 , 38 ].…”
Section: Incidencementioning
confidence: 99%
“…The time course of post-TIPS HE is defined by a steep rise in HE incidence in the first month after TIPS insertion, where liver function often takes a post-procedural hit [29]. The risk of new-onset episodic or recurrent HE remains high during the first year after TIPS but with the well-known post-TIPS improvement in muscle mass and fewer stressful events, the risk seemingly stagnates or declines [29][30][31][32][33][34]. Most cases of post-TIPS HE Despite recent clinical and procedural advancements, there has been no overall trend towards a decrease in incidence over the years, as illustrated by Figure 2, where studies are ordered according to the year when patient recruitment began (Figure 2) [17][18][19][20][21][22][23][24][25][26].…”
Section: Incidencementioning
confidence: 99%
“…Moreover, while all studies conducted have focused on sarcopenic assessment after TIPS, only one novel study has included the effect of TIPS on frailty parameters[ 218 ]. In this study, 12 cirrhosis patients showed improvement in skeletal muscle mass six months after TIPS compared to their baseline measurements before the procedure[ 218 ]. However, there was no improvement in LFI, handgrip strength, or physical performance measurements[ 218 ].…”
Section: Future Approaches In Frailty Managementmentioning
confidence: 99%
“…In this study, 12 cirrhosis patients showed improvement in skeletal muscle mass six months after TIPS compared to their baseline measurements before the procedure[ 218 ]. However, there was no improvement in LFI, handgrip strength, or physical performance measurements[ 218 ]. This study adds to the concerns about using TIPS as a potential therapy for cirrhotic frail patients.…”
Section: Future Approaches In Frailty Managementmentioning
confidence: 99%